The economic impact and the distribution of benefits and risk from the adoption of insect resistant (Bt) cotton in West Africa - Falck-Zepeda, José B.; Horna, Daniela; Smale, Melinda (International Food Policy Research Institute, 2007)
Cotton is the largest source of export receipts of several West African countries. Statistics however show a decreasing tendency in cotton yields and an increasing tendency in pesticide use. Under this circumstances there appear to be potential payoffs from the use of biotechnology products in the farming systems of the region. In this study we estimate different scenarios for the potential deployment of insect resistant cotton in selected countries in West Africa (WA). We use an economic surplus model augmented with a more rigorous sensitivity analysis of model parameters. Hypothetical scenarios of Bt cotton adoption in WA are simulated and single point values of model parameters are substituted with probability distributions. The scenarios include: no adoption in WA; adoption of existing varieties; adoption of WA varieties backcrossed with private sector lines; and fluctuating adoption patterns. According to the simulations, the total net benefits of adopting Bt seem to be small even after including the innovator surplus who accrues a larger share of the benefits. In contrast the WA countries included in the evaluation are worse off if they decide no to adopt Bt cotton. These results are in part explained by the conservative assumptions taken. The adoption pattern and the length of the adoption period affect the share of benefits earned by producers as compared to innovators. This study provides tools and information that can be used to build greater confidence in the process of setting agricultural research investment priorities.